Water wave scattering by an infinite step in the presence of an ice-cover - Ray, Swagata; De, Soumen; Mandal, B.N. (Zielona Góra: Uniwersytet Zielonogórski)
The classical problem of water wave scattering by an infinite step in deep water with a free surface is extended here with an ice-cover modelled as a thin uniform elastic plate. The step exists between regions of finite and infinite depths and waves are incident either from the infinite or from the finite depth water region. Each problem is reduced to an integral equation involving the horizontal component of velocity across the cut above the step.
Keywords: water wave scattering; ice-cover; infinite step; integral equation; Galerkin approximation; reflection coefficient; transmission coefficients